Adsorption of oil-grease from oil-in water dispersions on different thermal activated clay minerals - Turak, Fatma; Afsar, Miseyin (FREUND PUBLISHING HOUSE LTD, 2007)
Thermal activated clay minerals like montmorillanite, illite, muscovite and kaolinite were investigated to determine their adsorption capacity for removal of oil-grease from synthetically prepared oily water by batch adsorption. The clay samples used in this study were supplied from Marmara (used for ceramic industry) and Mediterranean regions in Turkey. In experimental studies, optimum values of pH, contact time, dosage of clays and particle size of the adsorbent were used. Natural clay samples were heated from 110 degrees C to 900 degrees C for I hour to obtain thermal activated clay samples. The oil retained after the adsorption is determined by UV spectrum of oil. In this method, percentage removals of oil-in water dispersions were observed from 78 to 94 %. The maximum adsorption capacity of oil-grease was accomplished when the illite clay was used. The order of adsorption capacity of oil-grease was illite > kaolinite similar to montmorillanite > muscovite. It was observed that the adsorption capacity decreases with increasing temperature.
Keywords: adsorption; oil-grease; thermal activated clay; WASTE-WATER; REMOVAL; Chemistry